2014
DOI: 10.1007/s10456-014-9424-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic markers of bevacizumab-induced hypertension

Abstract: Purpose There are currently no validated biomarkers predicting bevacizumab treatment outcome or toxicity. We combined biomarker data from six phase III trials of bevacizumab to assess whether genetic variation in vascular endothelial growth factor-A (VEGF-A) pathway or hypertension-related genes are associated with bevacizumab-induced hypertension. Experimental design Germline DNA was available from 1,631 patients receiving bevacizumab-containing therapy for advanced solid tumors. Overall, 194 white patients h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 53 publications
(57 reference statements)
0
16
0
Order By: Relevance
“…26 These authors also demonstrated that 6 different SNPs at loci involving the VEGF-A pathway, including VEGFR-1, VEGFR-2, VEGFR-3, EPAS1, and EGLN3, were associated with the development of bevacizumab-induced hypertension. 27 Schneider et al have evaluated SNPs at the VEGF-A locus in patients with metastatic breast cancer and their association with outcome and the development of hypertension. 9 Specifically, they found that 2 VEGF promoter SNP alleles, VEGF-2578AA and VEGF-1154A, were associated with better OS whereas 2 additional VEGF promoter SNP alleles, VEGF-634CC and VEGF-1498TT, were protective against hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…26 These authors also demonstrated that 6 different SNPs at loci involving the VEGF-A pathway, including VEGFR-1, VEGFR-2, VEGFR-3, EPAS1, and EGLN3, were associated with the development of bevacizumab-induced hypertension. 27 Schneider et al have evaluated SNPs at the VEGF-A locus in patients with metastatic breast cancer and their association with outcome and the development of hypertension. 9 Specifically, they found that 2 VEGF promoter SNP alleles, VEGF-2578AA and VEGF-1154A, were associated with better OS whereas 2 additional VEGF promoter SNP alleles, VEGF-634CC and VEGF-1498TT, were protective against hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen SNPs known to increase patients' susceptibility to hypertension and thrombosis were also included. These were not analyzed for their effect on bevacizumab treatment outcome, but for correlation with bevacizumab-induced hypertension; results were published recently [32]. After testing for minor allele frequency and the homogeneity of the observed allele frequency (Supplementary Fig.…”
Section: Laboratory Methodsmentioning
confidence: 99%
“…The development of hypertension is hypothesized to be due to reduced nitric oxide production and rarefaction of vessels (9,10). Hypertension in response to bevacizumab may also have a genetic component (11,12).…”
Section: Hypertensionmentioning
confidence: 99%